Confidential inquiry into families with two siblings with cystic fibrosis. Issue 6 (1st December 1997) - Lane, B; Williamson, P; Dodge, J A; Harris, H; Super, M; Harris, R
Abstract : OBJECTIVE: To audit the care that had been provided to couples before the birth of a child with cystic fibrosis where a sibling had been previously diagnosed. DESIGN: Retrospective review of case notes. SAMPLE: Families where at least one affected child had been born between 1 January 1991 and 30 June 1995 and the diagnosis in the first child was made before the second affected pregnancy reached 20 weeks. The combination of information on these families with data from the prenatal diagnosis register allowed the reconstruction of a cohort of pregnancies in women with a previous affected child. MAIN RESULTS: Forty six eligible families with a second affected child were identified. Details from the paediatrician who had diagnosed the first affected child were obtained in 43 cases: all 43 couples were offered genetic counselling, but where provided by a paediatrician this was difficult to assess as no couple was sent a summary letter. Details were obtained from the obstetrician in the subsequent affected pregnancy in 42 cases: prenatal diagnosis was not offered in 10 (24%), offered and declined in 24 (57%), offered and accepted but termination declined in eight (19%). In the overall cohort of at risk pregnancies, the estimated rate of prenatal diagnosis offer was 97%, prenatal diagnosis uptake 86%, false negative prenatal diagnosis rate 0%, and uptake of termination 95%. CONCLUSIONS: (1) Parental choice was an important determinant of second affected births. (2) Despite widespread availability, prenatal diagnosis was not offered in an estimated 3% of at risk pregnancies. (3) There were shortcomings in counselling documentation, in particular failure to send a summary letter to counselled couples.